Antioxidant and functional cosmeceutical properties of leaves of three melastomataceae species in nanoemulsion system for topical applications - Azahar, Nur Fauwizah (2019)
Melastomataceae commonly known as “Senduduk” has been recognized for its potential for the treatment of various ailments. The leaves of Melastoma malabathricum L., Clidemia hirta (L.) D. Don and Melastoma malabathricum varr. alba were studied for their antioxidant and functional cosmeceuticals properties. The levels of total antioxidant activities were evaluated using multiple assay and the result shows the correlation and cluster analysis (CA) were found that different antioxidant assays significantly correlated at (P<0.05). The high total antioxidant assay can be seen mainly from the ethyl acetate and methanolic extract of three Melastoma species. The functional cosmetic properties such as sun protection factor (SPF), anti-tyrosinase (whitening activity) and anti-microbial test were noticed to be influenced by the more polar solvents. The simplex centroid mixture design was found to be the best tools and was successfully developed the optimal ratio composed of 30:40:30 mixtures. The leaves of Melastoma leaves species exhibited positive result for tannin/polyphenolic, flavonoids and also saponin. Terpenes, terpenoids, hydrocarbon, fatty acid derivatives, phenol and carbohydrate (amino acids) were significant bioactive compounds identified in the Melastoma leaves using GCMS. Rutin and quercetin of flavonoid compounds were also detected using HPLC. The highlights of the development and characterization of nanoemulsion formulation revealed that the cream has smooth and silky texture and exhibited Melastoma nanoemulsion can act as natural photoprotective agents and natural inhibitors for elastase and collagenase activity on skin. The in vivo results showed Melastoma nanoemulsion can be used significantly as good moisturizing cream as it increases the hydration level and reduce the rate of transpiration (TEWL) after 30 minutes of application and presents as a good anti-wrinkles properties after four weeks of applications. Hence, the innovations of nanoemulsion of plant based materials containing active extract of Melastoma leaves yield good and effective cosmeceutical products particularly for improving skin conditions and ready to be utilized as one of the cosmeceutical ingredients.